Penentuan Harga Jual: Harga Pokok Produksi dan Ekspektasi Laba - Deri Firmansyah; Hari Mulyadi; Dwinanto Priyo Susetyo (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2023)
The purpose of this study is to analyze the relationship between cost of goods produced and profit expectations in influencing the determination of selling prices. This research uses a mix method approach. Research samples during 5 reporting periods with purposive sampling techniques. Secondary data as the primary source with time series data characteristics. A multiple linear regression model is selected and a model feasibility test is performed. Research findings, that the relationship between cost of goods produced and profit expectations can predict the determination of selling prices. The cost of goods produced and profit expectations have proven to have a positive and significant effect on determining selling prices, both individually and simultaneously. The implication, a selling pricing strategy requires complete cost information and the practice emphasizes conformity. Determination of selling prices as a determination of a strategy is quite complicated, the cost factor is not the only one considered. External factors beyond control remain the basis for consideration, as much as possible must be recognized to support the success of decision making on selling price strategies. The right conditions to increase or decrease the selling price of a product/service still require investigation. This can serve as a future research direction.